Preterm Multigravida with Two Previous Cesarean Deliveries and a Fetus with Asymmetric IUGR and Cleft Lip and Palate: A Case Report - Jhonatan, Senna Moca; Martadiansyah, Abarham; Bernolian, Nuswil; Mirani, Putri; Lestari, Peby Maulina; Agustria, Rizky; Arjanggi, Kiagus Irawan Satria (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Cleft lip and palate and intrauterine growth restriction (IUGR) are common congenital conditions and may suggest subtle genetic abnormalities. When no chromosomal defects are detected through standard testing, this combination presents a diagnostic challenge in prenatal care. . This case report presents a 33-year-old multigravida woman at 34 weeks of gestation, referred for suspected fetal growth restriction and cleft palate. Serial ultrasound examinations confirmed asymmetric IUGR along with a complete cleft involving the lip, alveolus, and palate. Elective cesarean delivery of pregnancy was performed at 36 weeks of gestation via cesarean section, with the infant diagnosed with unilateral cleft lip and palate. This case underlines the importance of considering advanced genetic testing in non-syndromic cases of CLP with IUGR. This case highlighting a gap in standard prenatal diagnostics and emphasizing the need for a broader genetic approach in such cases. Clinicians should remain alert and pursue early, comprehensive evaluation and multidisciplinary planning to ensure accurate diagnosis, timely intervention, and better neonatal outcomes.